The Role of Kedamangan in Preventing and Resolving Sexual Harassment Crimes in Pundu Village, Cempaga Hulu Sub-District, East Kotawaringin, Central Kalimantan - Hamisyah, Hamisyah; Suriani, Rollys; Pramita, Claudia Yuni (Journal of Law, Politic and Humanities, 2025)
Sexual harassment is a serious crime that requires a comprehensive approach, including local wisdom-based strategies. This study aims to analyze the role of Kedamangan (customary leadership) in preventing and resolving sexual harassment crimes in Pundu Village, Cempaga Hulu Sub-District, East Kotawaringin Regency, Central Kalimantan. The research employs an empirical juridical method with a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and document studies involving the Damang (customary leader), community figures, victims, and law enforcement officials. The findings reveal that Kedamangan plays a strategic role in prevention through customary education, dissemination of moral values, and social supervision rooted in Dayak local wisdom. In resolving cases, Kedamangan applies customary justice mechanisms prioritizing restorative principles, mediation, and communal reconciliation. The resolution process includes traditional rituals, payment of customary fines, and social sanctions aimed at restoring community social balance. Coordination between Kedamangan and formal law enforcement reflects a complementary collaborative pattern. The effectiveness of Kedamangan’s role is demonstrated by high community satisfaction and a low recurrence rate of similar cases. However, challenges remain, including limited understanding of formal legal systems and the need to strengthen the capacity of customary institutions in handling complex cases.